AUTOMATIC CHICKEN EGGS INCUBATOR 216 CAPACITIES - Marlon Tua Pangihutan Sibarani (RADJA PUBLIKA, 2025)
Poultry animals such as chickens incubate their eggs in a three weeks to hatch their eggs, which sometimes the egg yields are not optimal so that a poultry eggs incubator and its system are needed to optimize the results of hatching in which this built-in incubator with capacity 216 eggs with a rack system that rotates automatically, using a digital temperature and hygrometer sensor so that the temperature can be set at 38-39 0C and the humidity can be set at 55-70% according to the egg hatching temperature and humidity, and from the test results obtained the number of eggs that do not hatch and hatch both that hatch normally, defective and die, the research conducted, for chicken eggs, which originally amounted to 216 eggs to be hatched, 207 eggs that hatched well, 5 defective eggs and 3 eggs that died and 1 egg don’t have any embryos, and the result that this poultry egg incubator is capable of hatching poultry eggs normally above 96%.